Shared Escovopsis parasites between leaf-cutting and non-leaf-cutting ants in the higher attine fungus-growing ant symbiosis. Issue 9 (September 2015) - Meirelles, Lucas A.; Solomon, Scott E.; Bacci, Mauricio; Wright, April M.; Mueller, Ulrich G.; Rodrigues, Andre
Abstract : Fungus-gardening (attine) ants grow fungus for food in protected gardens, which contain beneficial, auxiliary microbes, but also microbes harmful to gardens. Among these potentially pathogenic microorganisms, the most consistently isolated are fungi in the genus Escovopsis, which are thought to co-evolve with ants and their cultivar in a tripartite model. To test clade-to-clade correspondence between Escovopsis and ants in the higher attine symbiosis (including leaf-cutting and non-leaf-cutting ants), we amassed a geographically comprehensive collection of Escovopsis from Mexico to southern Brazil, and reconstructed the corresponding Escovopsis phylogeny. Contrary to previous analyses reporting phylogenetic divergence between Escovopsis from leafcutters and Trachymyrmex ants (non-leafcutter), we found no evidence for such specialization; rather, gardens from leafcutters and non-leafcutters genera can sometimes be infected by closely related strains of Escovopsis, suggesting switches at higher phylogenetic levels than previously reported within the higher attine symbiosis. Analyses identified rare Escovopsis strains that might represent biogeographically restricted endemic species. Phylogenetic patterns correspond to morphological variation of vesicle type (hyphal structures supporting spore-bearing cells), separating Escovopsis with phylogenetically derived cylindrical vesicles from ancestral Escovopsis with globose vesicles. The new phylogenetic insights provide an improved basis for future taxonomic and ecological studies of Escovopsis .